Serum IgG, and IgM Levels in Children with Febrile Convulsions - Gulhis Deda; Ugur Karagol; Ya Vuz Gurer (Indonesian Pediatric Society Publishing House, 2018)
At the Dr. Sami Ulus Children's Hospital Ankara, Turkiye, 20 patients, twelve being between 6 months-2 year old and eight being between 2-4 years, with their first febrile convulsions (FC) were examined for serum IgG, IgA, IgM levels during the period of March 1989-]uly 1989. Twenty healthy children were used as controls, seven being between 6 months-2 years old and thirteen being between 2-6 years. The serum IgG, IgA and IgM levels of the patients between 6 months-2 years were 805.000 + 307.8984 mg/ dl, 49.7167 + 27.9807 mg/dl and i55.1833 + 62.9696 mg/dl respecttvelly. The serum IgG, IgA and IgM levels of the patients between 2-4 years were : 989.1250 ± 314.5359 mg/dl, 92.6125 ± 34.5663 mg/dl and 159.8750 ± 45.6647 mg.ldl respectivelly. The mean IgA levels of the 12 FC patients between 6 months-2years were 49.7167 ± 27.9807 mg/dl and the mean level of IgA in the age matched control group was 81.0427± 31.3551 mg/dl and the difference between them was statistically significant (p <0. 005). We conclude that FC under 2 years of age is associated with low serum IgA levels.